Iberoamerican scientific production on ICT in the educational context - Hernandez, Ronald M. (2021)
ICT in the educational context can be seen as information transmitting resources that link the teacher and the student in the improvement of teaching-learning adapted to the needs and characteristics of each subject. From this perspective, we seek to describe the state of Iberoamerican scientific production on the inclusion of ICT in the educational discipline in the period 2010 to 2020, based on a retrospective descriptive analysis of publications collected in journals indexed in Scopus. A total of n=1976 contributions were collected. It was found that production increased by 8.51%. Spain is the Iberoamerican country that contributes with the highest scientific production, authors with Iberoamerican affiliation usually publish through conference articles, highlighting ACM International Conference Proceeding Series. In front of an analysis of maturity of knowledge we are facing a development of scientific production in process of growth.